Avaliação da efetividade de programas de educação ambiental no licenciamento ambiental de hidrelétricas: o caso da UHE de Miranda - Amaro, Frederico Augusto Tavares (2021)
This research investigates the effectiveness of the Environmental Education Program (EEP) developed for environmental licensing of UHE Miranda. Its objective is to explore how PEA's are planned, conducted and developed within the scope of licensing and to create tools that contribute to their assessment, development and improvement. An investigation was carried out on the effectiveness of the EEP in the context of Environmental Impact Assessment (EIA) to develop and apply a set of 7 procedural effectiveness indicators and 13 substantive effectiveness indicators. The 02 components of the program were investigated, one aimed at the external public (EEP) and the other at the internal public, called the Workers' Environmental Education Program (WEEP). Using the elaborated indicators, 04 evaluation matrices were built to assign grade and concept to the investigated effectiveness categories applied to 9 activities of the EEP and 4 of the WEEP. The results obtained indicated compliance with procedural and substantive effectiveness for the investigated program in both categories. Despite this, it was not possible to obtain general considerations about the effectiveness of the PEA in the scope of licensing, since for this, it would be necessary to improve the indicators, analysis categories and investigated sample margin. Finally, it is expected that the set of indicators and the evaluation matrix elaborated will continue to be applied in the investigation of other PEA's and will be improved so as to allow for deeper investigations about the effective contributions arising from the PEA in society.